Yutub Kawasilati Taqyimi Maharati al-Kalami al-Lughati al-‘Arabiyyati - Dinata, Rahmat Satria; Musalwa, Musalwa (Universitas Islam Negeri Raden Intan Lampung, 2020)
The challenges of education in meeting millennial needs who are very familiar with technology and the internet are quite large. This is because their life experiences are different, especially their experience in using technology. The purpose of this research is to formulate a formula for evaluating Arabic speaking skills by using YouTube as an evaluation medium and seeing phenomena that emerge when Youtube is used as an evaluation medium in Arabic speaking skills courses. In this study, researchers used descriptive and analytical methods, because he dealt with a lot of information from students assigned to the class by observation and interview. The results showed that the steps in evaluating speaking skills included 3 stages, first the preparation or making of a video, then the upload stage and finally the assessment stage itself. while the phenomenon that arises when using youtube as an evaluation medium is the increased enthusiasm and motivation of students when speaking Arabic, especially when they know that they will publish it to YouTube students are more enthusiastic and serious in showing their speaking skills. with the use of youtube as an evaluation medium, it raises the phenomenon of increasing student scores, almost overall students get good grades, apart from that the videos they make can also be used as an interesting, fun, and easy learning media. In addition to these two results, evaluating speaking skills by speaking through videos uploaded on YouTube also makes the evaluation process construct valid.